SUPERGRAPHICS AND VIDEO ECOLOGY - Е.Nemtchinova Е. (Revista Gênero e Interdisciplinaridade, 2020)
The objective of this research was to conduct a study of supergraphics in the architecture and design of the visual urban environment in terms of video ecology. The article examined the specifics of supergraphics, its relationship with the concepts of graffiti and street art. The study also focuses on the specifics of new materials, innovative technologies for the implementation of supergraphics, in particular on the example of the subway. The variety of artistic techniques of supergraphics and its influence on the harmonization of the surrounding subject-spatial environment are revealed. The demand for supergraphics in modern conditions requires its deep analysis. The specifics of supergraphic tools are related to the requirements of creating an effective communicative human environment and solving a specific problem to improve the video ecology of the urban environment. The differences in the concepts of graffiti and street art are analyzed, their connection with the artistic techniques of modern supergraphics is outlined. The article provides new materials and innovative technologies. The provisions of the article reveal the inextricable connection of today’s trends in supergraphics with our modern life. The materials of the article contribute to further developments in the methodological material on this topic, help in the formulation of design tasks, as well as in the evaluation of the work in supergraphics.